A magnetic field- and frequency-dependent dynamic shear modulus model for isotropic silicone rubber-based magnetorheological elastomers. (1st March 2021) - Qiao, Yanliang; Zhang, Jiangtao; Zhang, Mei; Liu, Lisheng; Zhai, Pengcheng
Abstract: Both experimental and modeling studies on the dynamic shear storage and loss moduli of isotropic magnetorheological elastomers (MREs) were carried out in this work. Isotropic MREs were prepared based on silicone rubber filled with different contents of micro-sized carbonyl iron particles (CIPs). The magnetization characteristics of the prepared MREs and their dynamic shear moduli at a linear viscoelastic (LVE) strain and under different magnetic flux densities were measured. Based on the magnetization model of MREs, the magnetic dipole theory, and the quantitative analysis on the frequency-dependence of magneto-induced dynamic shear moduli, a new magneto-induced shear modulus model that was dependent on the CIP content and frequency was proposed. The model parameters can be simply determined. Combining with the generalized Maxwell viscoelastic model, that was used to describe the zero-field shear moduli of MREs, a new macroscopic magneto-viscoelastic constitutive model was developed to describe the magnetic field- and frequency-dependent shear modulus of the isotropic MREs with different CIP contents. The developed magneto-viscoelastic constitutive model was verified by comparing the model calculations with experimental data. The results showed that in the LVE strain state, the proposed magneto-viscoelastic model could accurately predict the dynamic shear storage and loss moduli of the isotropic MREs with different CIP contents in broad ranges of frequency and magnetic flux density using the unified model parameters. Graphical abstract: Image 1